A General Existence Theorem for von Neumann Economic Growth Models - Medvegyev, Peter (Econometrica, 1984)
[Results associated with Neumann-type economic growth models are described. We present a new generalization of the Neumann model with the idea of explaining and unifying certain basic results obtained by M. Morishima and J. L̵os̄ in proving general existence theorems. The idea of replacing constant input and output matrices in the Neumann model by those which depend continuously on the growth rate and on the price vector suggested and developed by Morishima, is coupled with an asymmetric-type generalization of the original Neumann model, developed by J. L̵os̄. Consequently, many of our results resemble and partly replace those obtained in both model generalizations.]